TAB Series-Resonant DC-DC Converter and Multi-Phase-Shift Based Global Optimization Modulation - Fengjiang Wu; Kaixuan Wang; Jianyong Su (Applied Sciences, 2022)
In this paper, a triple-active-bridge resonant dc-dc converter with the ability of topology-level power decoupling is proposed. The power coupling between the two dc ports is eliminated by adding a resonant capacitor to the common port. The operation principle and the steady-state power characteristics are analyzed. On this basis, a multi-phase-shift-based global optimization modulation is proposed to minimize the RMS values of the transformer currents in the entire power and voltage range, thus increasing the global efficiency. An experimental prototype is built to verify the correctness and availability of the proposed power decoupling topology and optimized modulation.